Kinetic Analysis of Molecular Permeabilities of Free‐Standing Polysaccharide Composite Films. Issue 3 (3rd November 2016) - Iijima, Kazutoshi; Kimura, Takayuki; Sato, Ryo; Takahashi, Tomoki; Hashizume, Mineo
Abstract : This study is performed in order to assess the molecular permeabilities of composite films of chondroitin sulfate C (CS) and chitosan (CHI) prepared by the hot press technique. Permeation behaviors are evaluated using horizontal diffusion cells and four substrates with different charges: methylene blue (MB), orange II (OR), l ‐tryptophan (Trp), and 4‐methylumbelliferyl β‐d ‐galactopyranoside (MUG). Permeability coefficients, diffusion coefficients, and partition coefficients are calculated from permeation curves. When MB and OR are used as the permeants, permeability coefficients in solutions with higher pH or ionic strength are greater than in those with lower pH or ionic strength. Permeability coefficients at pH 5.9 at which Trp carries zero net charge are as follows: Trp > MB ≈ MUG > OR. The diffusion coefficients and partition coefficients obtained indicate that CS/CHI films permeate these molecules based on a partition mechanism at lower pH and a pore model at higher pH. These characteristics appear to reflect the unique microenvironment of films consisting of polyion complexes of oppositely charged polysaccharides. Abstract : The permeabilities of composite films of chondroitin sulfate C (CS) and chitosan (CHI) prepared by the hot press technique are evaluated using horizontal diffusion cells and four substrates with different charges. A kinetic analysis indicates that CS/CHI films permeate molecules using a partition mechanism at lower pH, whereas a pore model is dominant at higher pH.